Hey,

I am currently having difficulties applying the chain rule to problems from what i can gather the chain rule is the derivative of the inside multiplied by the derivative of the outside

I tried working through a problem but screwed up somewhere,

The problem

find the derivative

$\displaystyle

k(x)=x^{2}sec(\frac{1}{x})

$

what I did

$\displaystyle k(x)=x^{2}sec(\frac{1}{x})$

=$\displaystyle 2x(secxtanx)\( \frac{x(0)-1(x)}{x}) $

=$\displaystyle 2x(secxtanx)(\frac{-1x}{x^{2}})$

=$\displaystyle 2x(secxtanx)(\frac{-1}{x})$

=$\displaystyle \frac{-2x(secx^{3})}{x}$

Am i on the right path